(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Despite global efforts to increase physical activity among children and adolescents, initiatives for physical activity in schools rarely have sustained impact. Interventions have been criticised for seeking to increase levels of physical activity by focusing on individual behaviour rather than considering the context and social structures in which individuals live their lives. This study examines whether and how the Walking School initiative promotes sustainable movement by integrating physical activity as a routine of the school day rather than adding physical activity. Methods: A mixed-methods participatory design was used, involving 14 pupils (six intervention and eight control classes) in lower-secondary school (12–16 years old) in Sweden. The intervention consisted of curriculum-based walking lessons held weekly for one semester, developed collaboratively by researchers, teachers, and students. Data sources included student surveys (pre-, mid-, and post-intervention), GPS tracking of lessons, researcher observations, and interviews with students and teachers. Quantitative data were analysed using Friedman, Wilcoxon, and Mann–Whitney U tests. Qualitative data underwent content analysis. Results: GPS data confirmed consistent walking activity during, on average, one lesson per week of 1.7 kilometres of walking at 3.4 kilometres per hour. A significant difference was found in students’ self-reported physical activity during school breaks where students in the intervention group perceived themselves as more physically active (p = .003). Surprisingly, no significant self-reported differences were found during lesson time. Qualitative data suggest that physical activity was positively perceived but seldom mentioned. The initiative was not experienced as physically demanding or intimidating. Students appreciated the opportunity to move, but it did not seem to be a primary focus for the students. Conclusion: The Walking School initiative illustrates how physical activity can be integrated into teaching practices in a way not perceived as disruptive or strenuous by students, which therefore has the potential to become a routine. These findings provide valuable insights into how health-enhancing physical activity can be fostered within the educational system. Support/Funding Source: This study was supported by the Swedish Research Council’s PhD programme “Sustainable Movement Education” through a PhD grant to the first author, Grant Number 2021-03830.